2023
DOI: 10.3390/ijerph20146361
|View full text |Cite
|
Sign up to set email alerts
|

Contact with Nature in Social Deprivation during COVID-19: The Positive Impact on Anxiety

Abstract: The 2019 outbreak of the novel coronavirus disease (COVID-19) had a devastating impact on millions of people worldwide. Following the constantly changing course of the pandemic, the Italian government massively restricted public and private life to prevent the further spread of the virus. Unfortunately, lockdown policies negatively impacted many people’s mental and physical health. Numerous studies recognized an essential role of urban green areas in promoting human well-being. The present study aims to evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 93 publications
1
1
0
Order By: Relevance
“…This study reinforces the critical importance of nature contact for mental well-being, a thesis consistently corroborated by the recent academic literature. Grounded in the previous work of Ningtyas et al [ 1 ], Fornara et al [ 3 ], James et al [ 16 ], and Costa et al [ 17 ], and complemented by Özgüner (2019), this research not only corroborates the restorative effects of engaging with natural environments on mitigating symptoms of stress, anxiety, and depression but also significantly extends these insights. By delving into the nuanced relationship between diverse patterns of nature contact and mental health outcomes, this study unveils the complex dynamics underlying this interaction, suggesting that the psychological benefits derived from nature are not universally consistent across different demographics but are influenced by the intensity, frequency, and type of nature engagement.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…This study reinforces the critical importance of nature contact for mental well-being, a thesis consistently corroborated by the recent academic literature. Grounded in the previous work of Ningtyas et al [ 1 ], Fornara et al [ 3 ], James et al [ 16 ], and Costa et al [ 17 ], and complemented by Özgüner (2019), this research not only corroborates the restorative effects of engaging with natural environments on mitigating symptoms of stress, anxiety, and depression but also significantly extends these insights. By delving into the nuanced relationship between diverse patterns of nature contact and mental health outcomes, this study unveils the complex dynamics underlying this interaction, suggesting that the psychological benefits derived from nature are not universally consistent across different demographics but are influenced by the intensity, frequency, and type of nature engagement.…”
Section: Discussionsupporting
confidence: 79%
“…This separation poses significant 2 of 14 implications for mental health, especially given the expanding body of evidence indicating that nature contact supports psychological well-being. Fornara et al [3] have shown how contact with nature can significantly reduce anxiety during times of social deprivation, such as the COVID-19 pandemic, highlighting the resilient role of nature in urban settings.…”
Section: Introductionmentioning
confidence: 99%